2019
DOI: 10.1177/0893318918821727
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Workers’ Organizational Temporality: Association With Cultural Time Orientation, Acculturation, and Mobile Technology Use

Abstract: Based on a meso-level model of organizational temporality, this study examined U.S. immigrant workers’ workplace temporal enactment and construal regarding cultural time orientation (monochronic vs. polychronic), acculturation type (assimilation, integration, segregation), and mobile technology use. Analyses revealed that cultural time orientation and acculturation type interacted to influence separated enactment of organizational temporality, and immigrant workers’ acculturation type and mobile use for work h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Time orientation has also been investigated with behavioral aspects like social networks using mixed methods analyses to understand their role in individual differences (Bertolotti et al, 2019). For US immigrant workers, monochronic versus polychronic time orientation influenced their cultural assimilation and use of technology to perform work (Lee and Flores, 2019). Researchers note that cross-country variations in time orientation have received limited attention in management literature (Lévesque and Stephan, 2020).…”
Section: Cultural Intelligence As the Theoretical Backgroundmentioning
confidence: 99%
“…Time orientation has also been investigated with behavioral aspects like social networks using mixed methods analyses to understand their role in individual differences (Bertolotti et al, 2019). For US immigrant workers, monochronic versus polychronic time orientation influenced their cultural assimilation and use of technology to perform work (Lee and Flores, 2019). Researchers note that cross-country variations in time orientation have received limited attention in management literature (Lévesque and Stephan, 2020).…”
Section: Cultural Intelligence As the Theoretical Backgroundmentioning
confidence: 99%
“…Few studies have addressed relationships between temporality and stress phenomena related to acculturation processes. For instance, a study that examined associations of cultural time orientation with acculturation on immigrant workers revealed that those characterized by integrated acculturation were primarily future-time oriented, somewhat present-time oriented, and interpreted organizational time as less urgent and scarce than those characterized by segregated acculturation (Lee & Flores, 2019). Regarding the specific construct of TP, one study reported that in Mexican Americans acculturation does not moderate the relationship between TP and psychological well-being (Romero, 2009).…”
Section: Time Perspectives and Acculturationmentioning
confidence: 99%
“…In particular, organizational scholarship has focused on how perceptions of time and the experience of time influence organizational processes and relationships as well as outcomes such as productivity, satisfaction, and effectiveness (Ancona et al, 2001;Ballard & Seibold, 2003;Orlikowski & Yates, 2002). Time and temporality are also central in studies of temporary and ad hoc organizing (Bakker et al, 2016), orientations to time expressed in and across cultures (Lee & Flores, 2019), the negotiation of visibility and invisibility in organizing (Cruz, 2017), contextual influences on discourses about career success and meaningful work (Hanchey & Berkelaar, 2015), and the temporal character and influence of ICTs in organizing (Leonardi et al, 2010).…”
Section: Time and Temporalitymentioning
confidence: 99%
“…Understanding the dominance and pervasiveness of particular ways of spending time and beliefs about time surfaces questions about control and how pervasive temporal structures exert influence (Bluedorn, 2008). For example, Lee and Flores (2019) found that Western temporal norms such as punctuality and the linear ordering of activities may be imposed on immigrant workers who have different temporal orientations. Indeed, the temporality of work is important because the kind of work done and the temporal organizing of work shape the sense of time for so many.…”
Section: Time and Temporalitymentioning
confidence: 99%